Relay selection for maximizing the number of successive transmission in cooperative networks. Issue 6 (2nd November 2017) - Wang, Jun; Wu, Qilin
Abstract: Relay selection has an important effect on improving the performance of cooperative communication system. However, the frequent operation of relay selection can bring enormous control message overhead, and then decrease the performance of cooperative communication. To reduce the relay selection frequency, in this paper, we propose a relay selection scheme to choose the best relay considering successive packets transmission. In this scheme, through the parameters of data transmission rate, the length of data packet and the estimated channel state information, the best relay is selected to maximize the number of successive packets transmission while guaranteeing the given outage probability. It is proven by numerical results that the proposed relay selection scheme can support the successive packets transmission in cooperative wireless networks and the maximum number of successive packets transmission is affected by the different network parameters, i.e. packet length, data transmission rate, signal to noise ratio and Doppler frequency. Compared to previous relay selection schemes by simulation results, it is shown that the proposed relay selection scheme can improve the throughput performance efficiently. Graphical abstract: Effect of data transmission rate on the maximum number of successive transmissions.